Thermal treatment of carbon fibre reinforced polymers (Part 1: Recycling). (January 2019) - Limburg, Marco; Stockschläder, Jan; Quicker, Peter
The increasing use of carbon fibre reinforced polymers requires suitable disposing and recycling options, the latter being especially attractive due to the high production cost of the material. Reclaiming the fibres from their polymer matrix however is not without challenges. Pyrolysis leads to a decay of the polymer matrix but may also leave solid carbon residues on the fibre. These residues prevent fibre sizing and thereby reuse in new materials. In state of the art, these residues are removed via thermal treatment in oxygen containing atmospheres. This however may damage the fibre's tensile strength. Within the scope of this work, carbon dioxide and water vapour were used to remove the carbon residues. This aims to eliminate or at least minimize fibre damage. Improved quality of reclaimed fibres can make fibre reuse more desirable by enabling the production of high-quality recycling products. Still, even under ideal recycling conditions the fibres will shorten with every new life-cycle due to production-based blending. Fibre disposal pathways will therefore always also be necessary. The problems of thermal fibre disintegration are summarized in the second part of this article (Part 2: Energy recovery).